2008 19th International Symposium on Software Reliability Engineering (ISSRE) 2008
DOI: 10.1109/issre.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Discovery Modeling Using Weibull Distribution

Abstract: A vulnerability discovery model describes the variation in the vulnerability discovery rate during the lifetime of a software system and can be used to assess risk and to evaluate possible mitigation approaches. A few vulnerability discovery models have recently been proposed. The AML Logistic model has been found to provide the best fit in several cases. Weibull distribution, which can model an asymmetric pdf, is often used for reliability evaluation in some fields but has not been used for modeling vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…Many VDMs assume that the total number of vulnerabilities in a vulnerable entity (i.e., software) is a time independent constant (e.g., [2], [18], [53]). Considering the combination of all releases as a single entity would severely violate this assumption since software keeps evolving to introduce new functionality, and thus keeps introducing new vulnerabilities over time.…”
Section: Vulnerability Count Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many VDMs assume that the total number of vulnerabilities in a vulnerable entity (i.e., software) is a time independent constant (e.g., [2], [18], [53]). Considering the combination of all releases as a single entity would severely violate this assumption since software keeps evolving to introduce new functionality, and thus keeps introducing new vulnerabilities over time.…”
Section: Vulnerability Count Methodsmentioning
confidence: 99%
“…Joh et al [18] proposed JW model, and compared it to AML on WinXP, Win2K3 and Linux (RedHat and RedHat Enterprise). The goodness-of-fit of JW was slightly worse than AML.…”
Section: Srgms and Defect Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamada et al [11] developed a software-reliability growth model incorporating the amount of test effort expended during the software testing phase. Joh et al [12] proposed a new Weibull distribution based on vulnerability discovery model. Sagar et al [13] presented best software reliability growth model with including feature of both Weibull distribution and inflection S-shaped SRGM to estimate the defects of software system, and provide help to researchers and software industries to develop highly reliable software products.…”
Section: Introductionmentioning
confidence: 99%
“…Omar and Malaiya have compared several VDMs by fitting the data for major operating systems data, and have shown that the AML models fits better than other models in most cases [15]. However since AML is symmetrical model, it might be not perform well for asymmetric behavior discovery rate, so in [16], the authors examined Weibull distribution which can model asymmetrical behaviors too. Woo et al [17,18] have examined the vulnerability discovery trends for sets of web browsers and HTTP servers using AML model.…”
Section: Introductionmentioning
confidence: 99%